2015
DOI: 10.1098/rspb.2015.0421
|View full text |Cite
|
Sign up to set email alerts
|

Foundation species' overlap enhances biodiversity and multifunctionality from the patch to landscape scale in southeastern United States salt marshes

Abstract: Although there is mounting evidence that biodiversity is an important and widespread driver of ecosystem multifunctionality, much of this research has focused on small-scale biodiversity manipulations. Hence, which mechanisms maintain patches of enhanced biodiversity in natural systems and if these patches elevate ecosystem multifunctionality at both local and landscape scales remain outstanding questions. In a 17 month experiment conducted within southeastern United States salt marshes, we found that patches … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
162
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 120 publications
(178 citation statements)
references
References 48 publications
8
162
2
Order By: Relevance
“…Ecologists are becoming increasingly aware that native foundation species provide ecosystem functions in nonlinear ways (39)(40)(41). Our experimental findings demonstrate similar nonlinearity in ecosystem functions provided by a nonnative foundation species that has invaded thousands of kilometers of coastline throughout the Northern Hemisphere.…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…Ecologists are becoming increasingly aware that native foundation species provide ecosystem functions in nonlinear ways (39)(40)(41). Our experimental findings demonstrate similar nonlinearity in ecosystem functions provided by a nonnative foundation species that has invaded thousands of kilometers of coastline throughout the Northern Hemisphere.…”
Section: Discussionsupporting
confidence: 61%
“…For example, functions such as wave attenuation and sediment stabilization may manifest on larger scales and at higher densities (39), whereas functions associated with biodiversity, such as productivity and nursery habitats, appear to operate on smaller scales and at lower densities (i.e., with early thresholds as shown here and in ref. 41). Although curve shapes of multifunctionality are likely to depend on the functions included in the analysis, our supplementary analysis (adding four processes measured at the end of our experiment) showed similarly curved functional responses, suggesting that our results are robust (Fig.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…On cobble beaches, for instance, many studies (including this one) have revealed non-trophic facilitation of the local community [23,42] and that at a scale of metres to tens of metres, cordgrass patches function as wave breaks to facilitate wave-sensitive forb species [43]. Similarly, intertidal mussel beds in the Wadden Sea were found to facilitate the community at a scale exceeding 100 m by baffling waves and changing sediment characteristics [24,44].…”
Section: Discussionmentioning
confidence: 99%
“…The role of ribbed mussels as a salt marsh facilitator has been explored for the past couple of decades in a variety of regions along the U.S. Atlantic Coast (Bertness and Leonard 1997, Angelini et al 2015. Ribbed mussels improve the marsh not only for the Spartina, but for the other organisms found there as well.…”
Section: Introductionmentioning
confidence: 99%